Trypanosoma cruzi infection imparts a regulatory program in dendritic cells and T cells via galectin-1-dependent mechanisms - Poncini, Carolina Verónica (2015)
Galectin-1 (Gal-1), an endogenous glycan-binding protein, is widely distributed at sites of inflammation and microbial invasion. Despite considerable progress regarding the immunoregulatory activity of this lectin, the role of endogenous Gal-1 during acute parasite infections is uncertain. In this study, we show that Gal-1 functions as a negative regulator to limit host-protective immunity following intradermal infection with Trypanosoma cruzi. Concomitant with the upregulation of immune inhibitory mediators, including IL-10, TGF-β1, IDO, and programmed death ligand 2, T. cruzi infection induced an early increase of Gal-1 expression in vivo. Compared to their wild-type (WT) counterpart, Gal-1-deficient (Lgals1-/-) mice exhibited reduced mortality and lower parasite load in muscle tissue. Resistance of Lgals1-/- mice to T. cruzi infection was associated with a failure in the activation of Gal-1-driven tolerogenic circuits, otherwise orchestrated by WT dendritic cells, leading to secondary dysfunction in the induction of CD4+CD25+Foxp3+ regulatory T cells. This effect was accompanied by an increased number of CD8+ T cells and higher frequency of IFN-γ-producing CD4+ T cells in muscle tissues and draining lymph nodes as well as reduced parasite burden in heart and hindlimb skeletal muscle. Moreover, dendritic cells lacking Gal-1 interrupted the Gal-1-mediated tolerogenic circuit and reinforced T cell-dependent anti-parasite immunity when adoptively transferred into WT mice. Thus, endogenous Gal-1 may influence T. cruzi infection by fueling tolerogenic circuits that hinder anti-parasite immunity.